Factors Affecting the Learning of Grade 12 HUMSS Students in Online Platforms in the New Normal Education at Bestlink College of the Philippines: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Education is the central concern of individuals, institutions, and countries for their development. As Covid-19 spread worldwide, advances in modern computer and network technology have driven the development of distance education. It made the education through E-Learning. Despite the current pandemic hindering education worldwide, online learning based on Internet services has become available and universal, facilitating the learning system.  The primary purpose of this study is to determine the factors affecting the learning of the Grade 12 HUMSS students in online platforms in the new normal education at Bestlink College of the Philippines. The researcher used the descriptive method as a research design. The researcher used surveys and questionnaires to gather data from the respondents. A total of sixty (60) respondents from the Grade 12 HUMSS students of Bestlink College of the Philippines are the study's respondents. A simple random sampling method was used to select a participant who will serve as a respondent. The results reveal that most students find coping with the new normal education system hard and difficult. In addition, they also experience problems such as learning environment, internet connection and time management. Undeniably, in some ways, the new normal education system affects the learning outcomes of the Grade 12 HUMSS students for them to accomplish their academic performances.
Keywords: Academic Performance; Factors; Learning Outcomes; Online Platforms; New Normal Education System